Pengaruh Pelaksanaan Meditasi Pernapasan Terhadap Penurunan Rasa Cemas Pada Penderita Fobia Gelap (Nyctophobia) (Studi Kasus Pada Karyawan CV. Shanghai Kop Relaksasi Mitraraharja) - Valdi Haris; Sutrisno; Surya R. Widya (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
This study aims to determine the effect of meditation on helping reduce anxiety in patients with dark phobia (Nyctophobia). This study uses a quasi-experimental research method and the results of the study are presented descriptively with purposive sampling conducted to CV employees. Shanghai Kop Mitraraharja Relaxation which has a dark phobia (Nyctophobia). Based on the results of the study, it was shown that breathing meditation had a good influence in reducing anxiety in patients with dark phobia, in which case the decrease was measured using the HARS (Hamilton Anxiety Rating Scale) questionnaire.